Letter from Georg Bredig to the Daniel Sieff Research Institute - Bredig, Georg (1937)
Fearing that his library might be destroyed under the Third Reich, Georg Bredig (1868-1944) offers to send his publications to the Daniel Sieff Institute in Rehovot, Palestine. The Daniel Sieff Research Institute was established in 1934 by Dr. Chaim Weizmann (1874-1952), a Russian-born biochemist and Zionist, who would become Israel's first president. The Daniel Sieff Research Institute was renamed The Weizmann Institute of Science in his honor in 1949.
Keywords: Jews, German--Intellectual life; Mekhon Ṿaitsman le-madaʻ; Weizmann, Chaim, 1874-1952; Bredig, Georg, 1868-1944; Third Reich